The Effect of Teacher Competence and the School Environment on Student Achievement of SD Negeri Kecamatan Jirak Jaya - Asrin; Fitria, Happy; Eddy, Syaiful (Jurnal Pendidikan Tambusai, 2021)
This study aims to analyze and describe: 1) the effect of teacher competence on student learning achievement; 2) the influence of the School Environment on Student Learning Achievement; and 3) the influence of teacher competence and school environment together on student learning achievement. This research uses quantitative methods. The results of the study state that: 1) there is an effect of teacher competence on student learning achievement; 2) there is an influence of the school environment on student achievement; and 3) there is an influence between Teacher Competence and School Environment together on Student Learning Achievement.